Communication strategies and media role to promote succesful breastfeeding - Emma Mirza Wati Mohamad (2007)
In the area of health communication, little focus is given to the study on breastfeeding promotion as opposed to other deadly health issues such as AIDS and cancer. This is rather sad given that the benefit of breastfeeding has been proven able to help prevent mothers and babies from developing some diseases in the future such as cancer, asthma and obesity. Hence, the purpose of this article is to look at the communication strategies, policies and media role in promoting health, specifically on breastfeeding initiatives. Based on findings from a study using three focus groups, it was found that information on breastfeeding is still very limited. The media especially television tend to promote information on formula milk which comes in the form of advertisements. However, most information on breastfeeding is obtained from the Internet. The study suggests that the media and the government should be more constant and proactive in disseminating more breastfeeding information to promote breastfeeding-friendly environment.